Factors related to adolescent women's readiness for menarche: menarche - Pratiwi, Debby; Br. Sembiring, Eliya Rosa; Marlina, Marlina (Institute Of Computer Science (IOCS), 2024)
Menarche is the first natural bleeding occurring in teenage women where blood comes out of the vagina or can be called the first menstruation. Menarche is an early sign of other changes such as breast growth, hair growth in the pubic and axillary areas, and fat distribution in the hip area. Objective: This research determines the factors related to the readiness of young women to face menarche in young women at Baitul Aziz High School, Percut Sei Tuan District, Deli Serdang Regency in 2023. This type of research is an Analytical Survey of researchers who try to explore how and why this phenomenon occurs and this research uses a cross-sectional approach, namely finding out what factors are related to the readiness of young women to face menarche. The sample used was 40 people. Data analysis in this study was univariate and bivariate analysis using the Chi-square test with a=0.05. Based on the results of the Chi-square statistical test, this research found that there was a relationship between the readiness of young women to face menarche, namely the knowledge factor with a p-value = 0.001, the attitude factor with a p-value = 0.000, and the family support factor with a p-value -value= 0.003 so all Ho are rejected (p<0.05). Baitul Aziz High School, Percut Sei Tuan subdistrict, Deli Serdang district, to foster more motivation, enthusiasm and increase knowledge when facing menstruation for the first time (menarche).